Peranan Guru dalam Menangani Perilaku Bullying Siswa di SMPN 2 Tinambung Kecamatan Balanipa Kabupaten Polewali Mandar - Andi Sugiati; Jumiati Nur; Salma Arizanti (Universitas of Muhammadiyah Makassar, 2019)
The main problem in this research is how the role of PPKn teachers in dealing with students' bullying behavior at Tinambung 2 Public High School in Pambusuang District, Polewali Mandar District, West Sulawesi Province. This study aims to determine the role of PPKn teachers in dealing with students' bullying behavior at Tinambung 2 Public High School in Pambusuang District, Polewali Mandar District, West Sulawesi Province. This type of research is an experiment consisting of two variables where there is a test given to the control class (before treatment) and the experimental class (after treatment). The method of data collection consists of three ways, namely: questionnaire, interview and documentation. The sample in this study was class VIII students. C and class VIII.D as many as 25 people each class. The results of the study show that, from the results of the independent test T-test samples (t test) it is known that the significance value of 0.123 ≥ 0.05, there is a significant value between the control class (before treatment) and the experimental class (after treatment). So to test the hypothesis it can be seen from the significance of two tailled, namely Ho is accepted if sig. 2 tailled ≥ 0.05 and Ho is rejected if sig. 2 tailled ≤ 0.05. So the hypothesis of this study was accepted because the value of sig 2 tailled ≥ 0.05 is (0.123 ≥ 0.05). So in this study the role of PPKn teachers in handling bullying behaviors of students at Tinambung 2 Public High School was done.Keywords : Role, teacher, Bullying behavior